Left Ventricular Systolic Function in Patients with Systemic Lupus Erythematosus and Its Association with Cardiovascular Events - Gegenava, Tea; Gegenava, Maka; Steup-Beekman, Gerda M.; Huizinga, Thomas W.J.; Bax, Jeroen J.; Delgado, Victoria; Marsan, Nina Ajmone (Journal of the American Society of Echocardiography, 2020)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disorder with potential cardiovascular involvement. The aim of this study was to assess left ventricular (LV) systolic function in a large cohort of patients with SLE using standard echocardiographic measurements and global longitudinal strain (GLS) by two-dimensional speckle-tracking analysis. Furthermore, the association between echocardiographic parameters and the occurrence of cardiovascular events was assessed. A total of 102 patients with SLE (88% women; mean age, 43 ± 14 years) undergoing a dedicated multidisciplinary assessment were analyzed, including echocardiography, at the time of their first visit. A control group consisted of 50 age- and sex-matched healthy subjects. Compared with control subjects, patients with SLE showed impaired LV systolic function on the basis of LV ejection fraction (51 ± 6% vs 62 ± 6%, P < .001) and by LV GLS (−15 ± 3% vs −19 ± 2%, P < .001). During a median follow-up period of 2 years (interquartile range, 1–6 years), 38 patients (37%) developed cardiovascular events. Kaplan-Meier survival curves showed that patients with SLE with more impaired LV GLS (on the basis of the median value of −15%) experienced higher cumulative rates of cardiovascular events compared with those with less impaired LV GLS (χ2 = 8.292, log-rank P = .004). On multivariate Cox regression analysis, LV GLS demonstrated an independent association with cardiovascular events (hazard ratio, 2.171; 95% CI, 1.015–4.642; P = .046), whereas LV ejection fraction was not significantly associated with the outcome. In patients with SLE, LV systolic function as measured by LV GLS is significantly impaired and associated with cardiovascular events, potentially representing a new tool to improve risk stratification in these patients. •In SLE patients, LV systolic function as measured by LV GLS is significantly impaired.•Impaired LV GLS in SLE patients is associated with cardiovascular events.•Assessment of LV GLS may significantly improve risk-stratification in SLE patients.